1)cos(альфа-бета)-сos(альфа+бета) 2)sin(пи/6 + альфа)+sin(5пи/6 + альфа) 3)корень из двух

1)cos(альфа-бета)-сos(альфа+бета)
2)sin(пи/6 + альфа)+sin(5пи/6 + альфа)
3)корень из двух

  • 1)cos(-)-cos(+)=coscos+sinsin-(coscos-sinsin)=coscos+sinsin-coscos+ sinsin=2sinsin

    2) sin(пи/6+альфа)+синус(5пи/6+альфа)=синусПи/6*косинусАльфа+косинусПи/6*синусАльфа+синус5пи/6*косинусАльфа+косинус5пи/6*синусАльфа=1/2*косинусАльфа+корень из трех/2*синусАльфа+1/2*косинусАльфа+(-корень из трех/2)*синусАльфа=2*1/2косинусАльфа=косинусАльфа

  • 1)cos(a-b)-cos(a+b)=cosa cosb+sina sinb -cosa cosb-sina sinb=0
    2)sin( пи/6+а)+sin(5пи/6+а)=sin (пи/6) cosa+cos(пи/6)sina+sin5пи/6 cosa+cos5пи/6 sina=1/2cosa+корень из 3/2 sina+1/2сosa-корень из 3/2 sina=сosa